Banded chaos in power systems. (IEEE Transactions on power delivery)
This paper focuses on one aspect of ferroresonance in power systems, i.e., the appearance of a strange attractor with a band-like structure. This attractor was called a ?pseudoperiodic? attractor in a previous paper where the phenomenon was first reported. It was found in this study that banded chaos arises from a sequence of period doubling bifurcations. Odd-subharmonics undergo a symmetry-breaking bifurcation before the period doubling cascade takes place. A theoretical discussion of symmetry-breaking and period doubling is given and a route to banded chaos in an actual power system is demonstrated. The Lyapunov exponents for the strange attractor were calculated